Respuesta agronómica de la habichuela (Vigna unguiculata, l).al tutorado y bayfolan forte - Minda Lastra, Cristina (2012)
During the understood period among April-Julio the 2012, an experiment was developed under field conditions, in the area of biotechnology of the University of Granma in the county of the same name, with the objective of evaluating the agronomic answer of the bean (Vigna Unguiculata, L) to the buoys and Bayfolan forte. The indicators were evaluated: height of the plants, I number of leaves, number of flowers / it plants, I number of sheaths / it plants, yield, weight of the sheaths of each treatment, I number of grains / sheath and longitude of the sheaths, also of the economic valuation. A block design was used at random with 4 treatments and 3 replicas, for stonemasons of 10 they were used it. 5 meters long and 1.20 of wide….